ISSUES THAT NEED TO BE RESOLVED WHEN DEVELOPING THE LEGAL FRAMEWORK OF INTERNATIONAL PRIVATE LAW RELATIONS IN METAVERSE - Jaloliddin Abdusatarov (Scholar Express Journals, 2023)
As the Metaverse continues to grow in popularity and functionality, there is a growing need to develop a legal framework that governs international private law relations. Such a framework must address several key issues, including jurisdictional conflicts, cross-border data privacy concerns, intellectual property rights, and contractual disputes. The lack of clarity in these areas can lead to legal uncertainty and hinder the growth of the Metaverse economy. Therefore, it is imperative for policymakers and legal experts to collaborate on developing a comprehensive legal framework that will provide clear guidelines for all stakeholders engaged in Metaverse activities. This annotation highlights the importance of addressing these issues and underscores the need for a collaborative effort in creating an effective legal framework for international private law relations in the Metaverse
Keywords: Jurisdiction; Cross-border transactions; Intellectual property